Occurrence of enterovirus infection in new-born children admitted to maternity ward in São Paulo municipality, Brazil (1980) - Waldman, Eliseu Alves; Fujita, Mitiko; Hutzler, Rudolf Uri; Ferrari, Flávio L.; Ayub, Munir A.; Pinto, Paulo R. P.; Matheus, José Guido; Kim, Jai S.; Cury, Paulo Cesar (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
The occurrence of intestinal infection with enterovirus was investigated in 300 healthy children of median age of two days old, born in hospital; the children were analysed before being discharged from hospital. For the investigation, these children were divided into three groups, and each group was composed by equal number of cases. The first group was examined during the period preceding The First National Day for Poliomyelitis Vaccination held in 1980; the second group was analysed soon after this mass immunization and the third after The Second National Day for Poliomyelitis Vaccination, which was achieved in the same year. On purpose of enterovirus investigation, it was analysed the single faeces sample obtained from every child by means of rectal swab. In 300 newborn children analysed, it was obtained poliovírus isolation in 13 (4.3%); among these eight belonged to the first group and five to the second group. From the infected children, twelve eliminated poliovírus 1 and one poliovírus 3. There were no isolation of other enteroviruses. It is considered the possibility of poliovírus infection by transplacental transmission either via delivery canal or through cross infection in hospital environment.